Effect of FSH and PMSG Additions on Maturation and Fertilization Rates of Bali Cattle Oocytes - Hasbi Hasbi; Herry Sonjaya; Andi Arya Pawarekki; Sri Gustina (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
The process of in vitro oocyte maturation requires stimulation of gonadotropin hormones, as well as in vivo. There are two gonadotropin hormones that are available in the market and can be used in the process, Follicle Stimulating Hormone (FSH) and Pregnant Mare Serum Gonadotropin (PMSG). This study aimed to determine the effect of the addition of FSH and PMSG hormones in the maturation medium on the in vitro maturation and fertilization rates of Bali cattle oocytes. This study had two treatments, the addition of FSH and PMSG, each of which was carried out 4 times. Oocytes matured in basic medium, M-199 plus Bovine Serum Albumin (BSA) 10 IU/ml, and 50 µg/ml Gentamycin. Furthermore, the matured oocytes fertilized in 80 μl drop of sperms. The data were analyzed by Chi Square test to determine the differences in the level of maturation and fertilization of Bali cattle oocytes in vitro. The results of this study indicated that there was no significant difference (P>0.05) between the addition of FSH and PMSG hormones in the maturation medium to the nuclear maturation rate (81.4 ± 2.2 vs 81.2 ± 2.3), and the fertilization rate (42.2 ± 4.3 vs 24.6 ± 2.7). It can be concluded that in vitro maturation and fertilization rate of Bali cattle oocytes with the addition of FSH and PMSG hormones to the maturation medium are similar, but showed a tendency for higher fertilization rate in the medium supplemented with FSH.